Promoting higher order thinking skills through outside classroom strategy in learning mathematics - Admon, Nor Delyliana (2015)
Mathematics is based on observations of assorted patterns with logically thinking that leads to various theories of abstract relations (Vale, 2012). The thinking process involves the skills of mathematical reasoning and creative thinking (Brodie, 2010). In Malaysia, mathematics education was introduced formally to each student since at early age. Mathematics has train them to think logically and systematically in solving problems and decision makings which can make them better in higher order thinking skills (HOTS). However, the process of learning and teaching in Malaysia secondary schools are still conventional (Bakar & Hadi, 2011; Hamdi et al., 2012). Teachers are prefer to choose traditional methods in order to manage the students easily (Rozita Radhiah & Abdul Rasid, 2012). If these situation are still adopted in Malaysia schools, the HOTS will not expanding as our wish as in the Malaysia Education Blueprint 2013-2025 (Malaysia Education Blueprint, 2013). In addition, most of the students think that mathematics is abstract (Pound, 2008). Therefore, according to research by Gainsburg (2008), they are an urgency of connecting mathematics in schools with real life situations. Outside classroom learning is a real learning where the students can involve and discover with their direct experience (Moffett, 2011). One of real life situations learning strategy is learning at outside classroom setting, which focusing on the use of learning techniques of 'hands-on ' and actively participating in the activity to gain knowledge (Waite, 2010). Students must put into practice ‘in the real world’ what they have theorized about. Beside that the learning can become inherently student-centered when moved from the boundaries of the classroom into the world at large. Therefore in this study, the researcher plan to integrate the strategy of learning outside the classroom in Mathematics learning to give students the chances to relate their theoretical into practical in real life situation.